Die Aufhebung der Zeit: Zur Utopie unbegrenzter Gegenwart in der Musik des 20. Jahrhunderts - Houben, Eva-Maria (Stuttgart Franz Steiner Verlag, 1992)
Since the beginning of the century, time has been the subject of artistic debate and philosophical discussion. If the concept of time itself is neither clearly definable nor manageable, the idea of a cancellation of time with regard to music as a so-called temporal art is even more difficult. This study is the first to provide a broad overview of the variety of ways in which 20th century music endeavoured to abolish the sequence of past, present and future and to dissolve temporal spaces. The utopia of the pure present, the spherical shape of time, becomes visible in numerous facets. ‘A book that is worth working through, because the wealth of evidence and the corresponding systematics provide an insight into the music of the 20th century that is far superior to a normal listing of individual pieces and composers.’ -Neue Zeitschrift für Musik ‘The examination of her thoughts and the material she has compiled is very exciting. Moreover, it is a book that in many respects virtually challenges (supplementary) criticism, a book that keeps you awake and heightens your own sensitivity to the central factor of time in music.’ -Dissonance .(Translated with DeepL.com)
Keywords: Time; Music philosophy and esthetics